A new species of Mysella Angas, 1877 from Southern Chile (Bivalvia: Galeommatoidea) - Güller, M. (2012)
Fil:Güller, M. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.